The predictors of and reasons for non-adherence in an observational cohort of patients with rheumatoid arthritis commencing methotrexate. (13th July 2019) - Hope, Holly F; Hyrich, Kimme L; Anderson, James; Bluett, James; Sergeant, Jamie C; Barton, Anne; Cordingley, Lis; Verstappen, Suzanne M M
Abstract: Objective: In order to develop interventions to optimize MTX use for the treatment of RA we evaluated the rate of, reasons for and predictors of MTX non-adherence during the first 6 months of therapy. Methods: The Rheumatoid Arthritis Medication Study (RAMS) is a prospective multicentre cohort study of incident MTX users in the UK. Prior to MTX commencement demographic, clinical and psychological data were collected. A weekly patient-completed diary recorded MTX dose, possible side effects and adherence over 26 weeks. The number of non-adherent weeks was calculated. Potential baseline predictors of ever non-adherence (⩾1 week non-adherent) during the first 6 months of MTX therapy were identified using logistic regression analyses. Results: 606 patients with RA were included; 69% female, mean (s.d. ) age 60 (13) years and DAS28 score 4.2 (1.2). Over the first 6 months following MTX initiation, 158 (26%) patients were ever non-adherent (71% intentional, 19% non-intentional, 10% unexplained) and mean (s.d. ) number of non-adherent weeks was 2.5 (2.1). Multivariable predictors of ever non-adherence included DAS28 [odds ratios (OR) 1.1, 95% CI 1.0, 1.4], fatigue (OR 1.1, 95% CI 1.0, 1.2 per cm), ⩾2 comorbidities vs no comorbidities (OR 1.9, 95% CI 1.1, 3.5) and high medication concerns despite perceived need (OR 1.1, 95% CI 1.0, 1.1 per unit decrease in need/concern differential). Conclusion: This is the largest study evaluating early intentional and non-intentional non-adherence to MTX, which has identified that patient beliefs and multi-morbidity strongly link with non-adherence. These findings can direct the design of and provide potential targets for interventions to improve patient adherence.